Analisis Pemilihan Karir yang Optimal bagi Mahasiswa Sistem Informasi Menggunakan Medote MOORA - Tangka, George Morris William; Edson Yahuda Putra (Jurnal Informatika dan Komputer, 2024)
Career selection is a crucial decision that significantly impacts an individual's future and job satisfaction, especially for Information Systems students who face various career opportunities amidst the rapid development of information technology and digital transformation. However, the complexity of these career choices poses challenges in determining the path that best aligns with their interests, skills, and aspirations. This research aims to analyze the factors influencing the optimal career selection for Information Systems students at the Faculty of Computer Science (FILKOM) and evaluate career alternatives based on specific criteria. The Multi-Objective Optimization by Ratio Analysis (MOORA) method was used to evaluate career choices based on criteria such as salary, work environment, career development, and other benefits. Data were collected through surveys and analyzed using the MOORA method. The research findings indicate that IT Project Manager is the most optimal career choice, followed by Digital Marketing and Entrepreneur. Based on these findings, it is recommended that students develop project management skills, seek internship opportunities in digital marketing, and hone entrepreneurial abilities to maximize their career prospects.